Efficacy and Safety of Very Short-Term Dual Antiplatelet Therapy After Drug-Eluting Stents Implantation for Acute Coronary Syndrome: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Zhong, Peng-Yu; Shang, Yao-Sheng; Bai, Nan; Ma, Ying; Niu, Ying; Wang, Zhi-Lu (Frontiers in Cardiovascular Medicine, 2021)
Background and objective: Dual antiplatelet therapy (DAPT) is the basis for preventing ischemic events after percutaneous coronary intervention (PCI), and 12 months DAPT has been the standard strategy recommended by guidelines. However, patients with acute coronary syndrome (ACS) have higher risk of thrombosis, and the application of very short-term DAPT (1-3 months) in patients with ACS is consistently controversial. The purpose of this study is to explore the efficacy and safety of 1-3 months DAPT in ACS patients with implanted drug-eluting stents. Method: We conducted a systematic review and meta-analysis of randomized controlled trials that compared the very short-term (3 months or less) with long-term (12 months or more) DAPT in patients with ACS after PCI. The randomized controlled trials were included by searching PubMed, EMBASE and Cochrane Library database. The relative risk (RR) and 95% confidence intervals for endpoint events were calculated by the fixed effects model, and trial sequential analysis was applied to calculate the anticipated sample size and assess the results. Result: A total of eight randomized controlled trials with 16,492 patients met inclusion criteria. There were no significant statistic differences in myocardial infarction (RR 1.05, 0.82–1.35, P=0.68), stents thrombosis (RR 1.32, 0.85–2.07, P=0.22), all-cause death (RR 0.87, 0.66–1.13, P=0.29), target vessel revascularization (RR 0.93, 0.76–1.13, P=0.47). However, there were significant differences in major bleeding (RR 0.60, 0.50–0.73, P <0.00001) and the net adverse cardiac and cerebrovascular events (RR 0.84, 0.74–0.95, P=0.007). Conclusions: The strategy of 1-3 months DAPT not only has a significant effect in ACS patients with implanted drug-eluting stents, but also reduces the risk of major bleeding. The scheme of short-term DAPT followed by P2Y12 receptor inhibitor monotherapy is especially beneficial for patients with ACS. The results of this systematic review and meta-analysis are based on the application of new generation drug-eluting stents and new oral antiplatelet drugs in patients with ACS, which are difficult to use in general population (Registered by PROSPERO, CRD 42020210520).